The relationship between mathematical communication skills and the attitude towards mathematics among students of the College of Basic Education (Journal of the College of Basic Education, 2022)
Few teachers master the skills of giving thought-provoking lectures and managing investigative discussion. Mathematical communication skills, such as listening, speaking and acting, are among the basic skills in teaching, which usually require many activities to be used by the teacher to develop and know their impact on learning. We can explain the importance of the current research as follows:- The importance of the university stage, which is one of the important stages in building and serving society.- The importance of the students of the College of Basic Education who will become teachers in the future, and their duty is to convey the scientific material correctly to their students and develop their attitudes and skills.- The importance of mathematical communication and its skills, which are an important part of the objectives of teaching mathematics in the general education stages.